A Convenient Method for the Synthesis of New 3-Hydroxy-5(2H)-Isoxazolone Derivatives from (Chlorocarbonyl)phenyl Ketene - Momeni Tikdari, Ahmad; Shokrani, Ali; Hamidian, Hooshang; Khabazzadeh, Hojatollah (Asian Journal of Chemistry, 2016)
The synthesis of new 5(2H)-isoxazolone derivatives has received considerable amount of attention. This class of heterocycle ring systems can undergo 1,3-dipolar cycloaddition reactions. The new derivatives synthesis was achieved by the reaction of meso-ionic compounds with p-amino thiophenol as a nucleophile.